The Impact of Mobile-Assisted Language Learning on Reading Engagement of English Majors - Sheng, Shan (Journal of Educational Research and Policies, 2025)
This study investigates how mobile-assisted language learning (MALL) shapes English majors’ reading engagement through a tripartite framework encompassing cognitive, behavioral, and affective dimensions. By conducting comparative analyses between mobile learning environments and traditional classroom settings, the research reveals that contextualized task design and adaptive intelligent algorithms inherent in mobile platforms fundamentally restructure learners’ behavioral patterns and emotional investment trajectories. Empirical findings demonstrate that instant feedback mechanisms and microlearning opportunities offered by mobile technologies effectively enhance learning motivation and cognitive adaptability. However, these advantages coexist with heightened risks of attentional fragmentation and technology overreliance. The study advocates for pedagogical strategies that strategically balance technological empowerment with fundamental teaching principles, proposing an integrated ecosystem that synergizes classroom instruction with mobile learning experiences. These insights provide both theoretical grounding and practical guidelines for optimizing language education within digital transformation initiatives.